Programs from Proofs of Predicated Dataflow Analyses - Jakobs, Marie-Christine; Wehrheim, Heike (Proceedings of the 30th Annual ACM Symposium on Applied Computing)
Programs from Proofs" is a generic method which generates new programs out of correctness proofs of given programs. The technique ensures that the new and given program are behaviorally equivalent and that the new program is easily verifiable, thus serving as an alternative to proof-carrying code concepts. So far, this generic method has one instantiation that verifies type-state properties of programs. In this paper, we present a whole range of new instantiations, all based on data ow analyses. More precisely, we show how an imprecise but fast data ow analysis can be enhanced with a predicate analysis as to yield a precise but expensive analysis. Out of the safety proofs of this analysis, we generate new programs, again behaviorally equivalent to the given ones, which are easily verifiable" in the sense that now the data ow analysis alone can yield precise results. An experimental evaluation practically supports our claim of easy verification.

Systematik zur Entwicklung einer produktlebenszyklusorientierten Geschäftsmodell-Roadmap - Peitz, Christoph

Systematik zur frühzeitigen Absicherung der Sicherheit und Zuverlässigkeit fortschrittlicher mechatronischer Systeme - Dorociak, Rafal

Augmented & Virtual Reality in der Produktentstehung: Grundlagen, Methoden und Werkzeuge; Interaktions- und Visualisierungstechniken, Virtual Prototyping intelligenter technischer Systeme mit AR/VR - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Systematik zur wirtschaftlichkeitsorientierten Konzipierung Intelligenter Technischer Systeme - Vaßholz, Mareen

Verification and Simulation of Self-Adaptive Mechatronic Systems - Heinzemann, Christian

Optimizing Water Tanks in Water Distribution Systems by combining Network Reduction, Mathematical Optimization and Hydraulic Simulation - Hallmann, Corinna; Suhl, Leena (OR Spectrum)
In the last two decades, water consumption in Germany has been decreasing, which causes the water tanks and pipes in water distribution systems to work inefficiently. This paper proposes a method that supports the planning process for tanks in water distribution systems. The method uses a combination of network reduction, mathematical optimization and hydraulic simulation. The mathematical optimization model is a non-convex Mixed Integer Quadratically Constrained Program (MIQCP) that is solved by a piecewise linearization. As this may lead to many binary variables and therefore high computing times, the size of the water distribution system model is reduced before building the optimization model. After applying several network reduction techniques and using a piecewise approximation of the original model, there may be some hydraulic differences between the original network model and the reduced network model. To make sure that the solution obtained in the optimization process is feasible in the original water distribution system model, the solution is verified by a hydraulic simulation. If the solution is not feasible, the reduced model has to be modified and solved again until the hydraulic simulation verifies a solution as feasible. In this paper, each of these processes is described and the results indicate the usefulness of each of them.

Homodyne detection with on-off detector systems - Lipfert, T.; Sperling, Jan; Vogel, W. (Physical Review A)

Continuous sampling of the squeezed-state nonclassicality - Agudelo, E.; Sperling, Jan; Vogel, W.; Köhnke, S.; Mraz, M.; Hage, B. (Physical Review A)

Unified nonclassicality criteria - Ryl, S.; Sperling, Jan; Agudelo, E.; Mraz, M.; Köhnke, S.; Hage, B.; Vogel, W. (Physical Review A)

Convex ordering and quantification of quantumness - Sperling, Jan; Vogel, W (Physica Scripta)

Entanglement and phase properties of noisy NOON states - Bohmann, M.; Sperling, Jan; Vogel, W. (Physical Review A)

Entanglement witnesses for indistinguishable particles - Reusch, A.; Sperling, Jan; Vogel, W. (Physical Review A)

Nonclassicality Phase-Space Functions: More Insight with Fewer Detectors - Luis, Alfredo; Sperling, Jan; Vogel, Werner (Physical Review Letters)

Balanced homodyne detection with on-off detector systems: Observable nonclassicality criteria - Sperling, Jan; Vogel, W.; Agarwal, G. S. (EPL (Europhysics Letters))

Full Multipartite Entanglement of Frequency-Comb Gaussian States - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Optimizing Software-Defined Networks using Application-Layer Knowledge - Wette, Philip

An overview of the BIOASQ large-scale biomedical semantic indexing and question answering competition - Tsatsaronis, George; Balikas, Georgios; Malakasiotis, Prodromos; Partalas, Ioannis; Zschunke, Matthias; R. Alvers, Michael; Weissenborn, Dirk; Krithara, Anastasia; Petridis, Sergios; Polychronopoulos, Dimitris; Almirantis, Yannis; Pavlopoulos, John; et al. (BMC Bioinform.)

Linked SDMX Data: Path to high fidelity Statistical Linked Data - Capadisli, Sarven; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

Semantic Quran - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Semantic Web)